First record of the genus Systenus Loew (Diptera: Dolichopodidae) from Colombia, with description of four new species - Ramos-Pastrana, Yardany; Merchan-Vargas, Geraldine Lucia; Soares, Matheus M.m. (Zootaxa, 2024)
The genus Systenus Loew, 1857 (Dolichopodidae: Medeterinae) is recorded for the first time from Colombia through the description of four new species: S. bickeli sp. nov., S. colombiensis sp. nov., S. fuscus sp. nov. and S. grossus sp. nov. and by the record of five previously described species: S. beatae Naglis, S. flaviatus Naglis, S. maculipennis Bickel, S. naranjensis Bickel and S. parkeri Bickel. A key to the males, high resolution photographs and distribution map of the nine Colombian species are provided.